2000
DOI: 10.4049/jimmunol.165.6.3198
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Up-Regulates IL-18 Gene Expression Via IFN Consensus Sequence-Binding Protein and Activator Protein-1 Elements in Macrophages

Abstract: Constitutive IL-18 expression is detected from many different cells, including macrophages, keratinocytes, and osteoblasts. It has been known that IL-18 gene expression is regulated by two different promoters (p1 promoter and p2 promoter). When RAW 264.7 macrophages were treated with IFN-γ, IL-18 gene expression was increased in a dose- and time-dependent manner. IFN-γ activated the inducible promoter 1, but not the constitutive promoter 2. Mutagenesis studies indicated that an IFN consensus sequence-binding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 48 publications
7
62
0
Order By: Relevance
“…3A), indicating the requirement of an additional signaling pathway to TLR4/ MyD88 for the active IL-18 induction. It is also reported that IFN-␥ and LPS up-regulate IL-18 gene expression via IFN consensus sequence-binding protein and AP-1 elements in macrophages (41), which may be the mechanism of the IFN-␥ and LPS effects in this study. In support of this, the expression of 24-kDa proIL-18 protein was not reduced in the lysate of the cells treated with LPS and PR3 after IFN-␥ priming, even though 18-kDa IL-18 was markedly generated in the cell lysate and supernatant by the treatment (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…3A), indicating the requirement of an additional signaling pathway to TLR4/ MyD88 for the active IL-18 induction. It is also reported that IFN-␥ and LPS up-regulate IL-18 gene expression via IFN consensus sequence-binding protein and AP-1 elements in macrophages (41), which may be the mechanism of the IFN-␥ and LPS effects in this study. In support of this, the expression of 24-kDa proIL-18 protein was not reduced in the lysate of the cells treated with LPS and PR3 after IFN-␥ priming, even though 18-kDa IL-18 was markedly generated in the cell lysate and supernatant by the treatment (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Accumulated evidence indicates that ICSBP and PU.1 activate transcription through Ets-IRF DNA elements and related elements in IFN-␥-stimulated macrophages, as reported for IL-1␤ and the respiratory oxidase gene gp91 phox (44 -46). ICSBP and PU.1 may also have a role in enhancing expression of the toll-like receptor 4 and IL-18 through a similar element (47,48). This activation seems to involve other factors, notably the co-activator/histone acetylase cAMP-response element-binding protein-binding protein/p300, with which PU.1 has been shown to interact (49).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inhibitory effect of heat shock on IL-18 expression is related to the interference of the JNK/AP-1 signaling pathway (24). Recent studies revealed that AP-1 is involved in regulating the expression of IL-18 (25), suggesting that the JNK/AP-1 signaling pathway could have a critical role in mediating the production of IL-18. In the present study, we have shown a direct effect of IL-18 on cardiac fibrosis.…”
Section: Control Group Fructose Group Ms-gfp Group Ms-il-18 Groupmentioning
confidence: 99%